2002
DOI: 10.3758/bf03192907
|View full text |Cite
|
Sign up to set email alerts
|

Preference and resistance to change in concurrent variable-interval schedules

Abstract: Response strength is a theoretical construct that has been related to empirical measures in a variety of ways. Skinner (1938) proposed the concept of reflex reserve, which he measured by resistance to extinction.Later, after abandoning reflex reserve (e.g., Skinner, 1950), he invoked probability of respondingas the measure of strength,with response rate serving as a surrogate for probability. Herrnstein (1970) proposed choice behavior as a more appropriate measure, on the basis of his demonstration of orderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 29 publications
8
18
1
Order By: Relevance
“…All data points were below 0.0, indicating systematically greater preference for the VI 40(Lean) stimulus. Further, preference in the present study approximated preference obtained in previous studies (Belke, ; Bell & Williams, ; Gibbon, ). To be consistent with these previous studies, we express preference differently here, as a proportion of response rates to the VI 40(Lean) stimulus relative to response rates to the VI 40(Rich) stimulus.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…All data points were below 0.0, indicating systematically greater preference for the VI 40(Lean) stimulus. Further, preference in the present study approximated preference obtained in previous studies (Belke, ; Bell & Williams, ; Gibbon, ). To be consistent with these previous studies, we express preference differently here, as a proportion of response rates to the VI 40(Lean) stimulus relative to response rates to the VI 40(Rich) stimulus.…”
Section: Resultssupporting
confidence: 88%
“…Bell and Williams () suggest that their findings reveal a limitation to the generality of the relation between preference and resistance to disruption. Bell and Williams, however, assessed preference with brief extinction probes, a different procedure from that used by Nevin and colleagues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to presession feeding and decreased sample duration were similar between trial types, whereas resistance to extinction was greater for the leaner trial type during the 1:9 and 9:1 conditions. Although they are inconsistent with sensitivity of baseline accuracy, these findings are consistent with previous findings in concurrent-choice situations that have shown no clear pattern of resistance to disruption as a function of different reinforcement rates between two alternatives (e.g., Bell & Williams, 2002; McLean & Blampied, 1995; McLean, Campbell-Tie, & Nevin, 1996; Nevin et al, 1990). While they resembled the present findings with presession feeding and extinction, however, these previous studies nevertheless revealed greater overall resistance to disruption of responding on both alternatives in components arranging higher reinforcement rates.…”
Section: Discussionsupporting
confidence: 75%
“…Here, too, results differ depending on whether one or two stimuli are presented simultaneously. When multiple schedules are used (akin to our Experiment 1), greater resistance to change in the richer schedule is observed, but when training involves concurrent schedules (akin to our Experiment 2), there is no differential resistance to change across the two concurrently presented alternatives, despite differences in reinforcement frequency for the two alternatives (Bell & Williams, 2002).…”
Section: Discussionmentioning
confidence: 98%